Bending and free vibration analysis of sandwich plates with functionally graded soft core, using the new refined higher-order analysis model. (February 2021) - Ye, Renchuan; Zhao, Na; Yang, Desen; Cui, Jie; Gaidai, Oleg; Ren, Peng
This study presents a new higher-order refined analysis model for static and free vibration analysis of a sandwich plate with soft functionally graded material core. The governing equations are derived from equilibrium differential equations of motions. The accuracy and convergence of the present model and numerical solution are validated versus available results. Variable length width ratios, thickness ratios between skins and core and span-to-thickness of sandwich plates have been studied. Obtained results show that suggested model can achieve greater accuracy for sandwich plates with soft functionally graded material core, as compared to existing functionally graded sandwich plate analysis models and models based on finite element method. Finally, parametric study has been carried out to investigate influence of volume fraction distribution, thickness to side ratio and material properties on the plate bending and free vibration.